PSYCHOEDUCATION INTERVENTION INCREASE ON THE ABILITY OF THE PRE-SENILE HYPERTENSION MANAGEMENT - Nyoman Sudja; Meirina Meirina (Universitas Airlangga, 2017)
Introduction: Increasing age in pre-senile, causes a deterioration abilities and physical changes, including the cardiovascular system. Blood vessels lose their elasticity thus be increased peripheral vascular resistance that results in hypertension. This study aims to gain an idea of the effect on the ability of pre-senile people's psychoeducation in the management of hypertension. Method: Quasi-experimental, the pre-post test with control group design, psychoeducation intervention with a sample size of 72 people . Result: The results showed signifi cant difference of pre-aged knowledge and behavior before and after getting psychoeducation intervention in the intervention group (p-value = 0.000 knowledge, and behaviors = 0.000) . Whereas in the control group there was no difference in knowledge (p-value = 0.896), but there are signifi cant differences in behavior of pre-senile people (p-value = 0.049). There are differences in knowledge and behavior after they were given psychoeducation intervention (post-test ) in the intervention group and the control group (p-value = 0.001 knowledge , behavior=0.018). Discussion: Psychoeducation had effect on the ability of pre-senile in the management of hypertension, so this program can be applied to groups of Posbindu for pre-senile people throughout the areas of the city of Bogor. Key words: psychoeducation, skills, pre-senile, hypertension